The SAGE handbook of media and migration - Smets, Kevin; Leurs, Koen; Georgiou, Myria; Witteborn, Saskia; Gajjala, Radhika (SAGE Reference)
Migration moves people, ideas and things. Migration shakes up political scenes and instigates new social movements. It redraws emotional landscapes and reshapes social networks, with traditional and digital media enabling, representing, and shaping the processes, relationships and people on the move. The deep entanglement of media and migration expands across the fields of political, cultural and social life. For example, migration is increasingly digitally tracked and surveilled, and national and international policy-making draws on data on migrant movement, anticipated movement, and biometrics to maintain a sense of control over the mobilities of humans and things. Also, social imaginaries are constituted in highly mediated environments where information and emotions on migration are constantly shared on social and traditional media. Both, those migrating and those receiving them, turn to media and communicative practices to learn how to make sense of migration and to manage fears and desires associated with cross-border mobility in an increasingly porous but also controlled and divided world.